Interactions between Trypanosoma cruzi Secreted Proteins and Host Cell Signaling Pathways - Watanabe Costa, Renata; da Silveira, Jose F.; Bahia, Diana (Frontiers in Microbiology, 2016)
Chagas disease is one of the prevalent neglected tropical diseases, affecting at least 6-7 million individuals in Latin America. It is caused by the protozoan parasite Trypanosoma cruzi (T. cruzi), which is transmitted to vertebrate hosts by blood-sucking insects. After infection, the parasite invades and multiplies in the myocardium, leading to acute myocarditis that kills around 5% of untreated individuals. T. cruzi secretes proteins that manipulate multiple host cell signaling pathways to promote host cell invasion. The primary secreted lysosomal peptidase in T. cruzi is cruzipain, which has been shown to modulate the host immune response. Cruzipain hinders macrophage activation during the early stages of infection by interrupting the NF-kB P65 mediated signaling pathway. This allows the parasite to survive and replicate, and may contribute to the spread of infection in acute Chagas disease. Another secreted protein P21, which is expressed in all of the developmental stages of T. cruzi, has been shown to modulate host phagocytosis signaling pathways. The parasite also secretes soluble factors that exert effects on host extracellular matrix, such as proteolytic degradation of collagens. Finally, secreted phospholipase A from T. cruzi contributes to lipid modifications on host cells and concomitantly activates the PKC signaling pathway. Here we present a brief review of the interaction between secreted proteins from T. cruzi and the host cells, emphasizing the manipulation of host signaling pathways during invasion.